2017
DOI: 10.1111/1750-3841.13845
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multiplex PCR Assay for Detection of Pseudomonas fluorescens with Biofilm Formation Ability

Abstract: A mPCR assay targeting adnA and fliC genes showed rapid and reliable detection of P. fluorescens with biofilm formation ability, which could be useful to detect this contamination in milk samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…For pseudomonads, two non-quantitative multiplex PCR approaches have been performed for different Pseudomonas species in meat (Ercolini et al 2007) and of P. fluorescens strains with a biofilm-forming ability (Xu et al 2017). However, until now, no qPCR assay has been developed for the simultaneous quantification of various milk-spoiling Pseudomonas species in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For pseudomonads, two non-quantitative multiplex PCR approaches have been performed for different Pseudomonas species in meat (Ercolini et al 2007) and of P. fluorescens strains with a biofilm-forming ability (Xu et al 2017). However, until now, no qPCR assay has been developed for the simultaneous quantification of various milk-spoiling Pseudomonas species in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was successfully used in meat and dairy processing environment for the isolation of P. fluorescens oligotypes (Stellato et al 2017). Another study reported the use of multiplex PCR for the detection of P. fluorescens showing the ability of biofilm formation with a detection limit of target strain to 10 2 cfu/ml (Xu et al 2017).…”
Section: Enzymes Of P Fluorescensmentioning
confidence: 99%
“…To reduce the frequency of contamination and to eliminate the niche populations for these organisms in food production and processing systems, different identification and tracking methods have been developed (Martin et al, 2011). However, the high genetic and genomic diversity within the P. fluorescens complex (Garrido-Sanz et al, 2016) found in cheese samples requires running different phenotypic tests, such as API 20 NE (Martin et al, 2011), MALDI-TOF (Hrabák et al, 2013), and distinct genotypic techniques, such as PCR (Scarpellini et al, 2004;Xu et al, 2017), 16S rRNA sequencing (Caputo et al, 2015;Cenci-Goga et al, 2014;Chierici et al, 2016;Garrido-Sanz et al, 2016), pulsed-field gel electrophoresis (PFGE; Martin et al, 2011;Carrascosa et al, 2015), and MLSA (Andreani et al, 2015a,b;Gomila et al, 2015;Chierici, 2016;Garrido-Sanz et al, 2016), to avoid making mistakes in their correct identification.…”
Section: Introductionmentioning
confidence: 99%